Upaya Sekolah dalam Mengembangkan Perilaku Prososial pada Anak Usia Dini di TK Ya BAKII Kesugihan - Hanita, Ifa Refli; Zalfa, Khulaimata; Retnaningrum, Wulandari (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
The importance of developing prosocial behavior from an early age is based on the development of children who are in the preoperational phase, so that children have egocentric tendencies. Educators, as those responsible for developing prosocial behavior in the realm of education, require educators to have a comprehensive picture of the social behavior of their students. Apart from that, in the development process educators must use appropriate efforts or strategies to achieve prosocial behavior in their students. This research aims to determine educators' efforts to develop prosocial behavior in students at Kindergarten Ya BAKII Kesugihan. This research method is a qualitative method with a phenomenological approach. Data collection techniques in this research are: interviews and observation with supporting data from documentation. Meanwhile, data analysis uses the Milles and Hubberman model with stages of data reduction, data presentation and conclusion drawing. The results of this research show that the efforts used in Kindergarten Ya BAKII Kesugihan to develop social behavior are the use of strategies in the form of stimulation integrated with learning values presented in group form, implementing positive things in the daily activities of students and providing stories or exemplary stories. Then, to support the process of developing prosocial behavior, there are rewards to increase students' learning motivation.